GAMBARAN SIKAP ORANG TUA TERHADAP MODEL DAN TIPE POLA ASUH PADA ANAK USIA PRA SEKOLAH DI TK PAUD RINJUNGU PAHAMU DI DESA KAMBATATANA KABUPATEN SUMBA TIMUR - FAIQATUL MUNAWAROH; MARTHA METI KODY; ULY AGUSTINE; YOSEPHINA ELIZABETH SUMARTINI GUNAWAN (Poltekkes Kemenkes Kupang, 2017)
Introduction: Parenting patterns of good and true parents in children will affect the personality of pre-school age children. The purpose of this study is to know the description of parental attitudes toward the model and type of parenting pattern in pre-school age children in TK PAUD Rinjungu Pahamu Kambatatana Village, East Sumba regency. Method: This research is descriptive study to know the description of parent attitude toward model and type of parenting pattern in pre school children, with sampling technique total sampling 35 respondents. Result: Model of parent and follower pattern that approve as much as 65,71%, Pancasila parenting model that approve as much as 68,57%. The authoritarian parenting pattern that approves as much as 65.71%. Approved democratic parenting as much as 74.28%. Laisesz-faire parenting pattern that does not approve as much as 74.28%. Conclusion: most of the respondents apply good parenting to the child. Thus it is advisable for parents to guide using the democratic parenting pattern because it is always strong, be a child can grow into a person well.